Bioprospecting Microalgae: A Systematic Review of Current Trends - Juan S. Chiriví-Salomón; Steven García-Huérfano; Ivan A. Giraldo (Phycology)
The growing interest in microalgae is driven by their potential in various bioindustries, such as biofuel production, bioremediation, and the generation of high-value biomolecules. This paper aims to systematically review the state of research on bioprospecting microalgae, their applications, and recognize trends. This study employs an exploratory and descriptive research approach, using bibliometric methods to analyze scientific production and identify emerging trends in bioprospecting microalgae research. The analysis reveals exponential publication growth, with multidisciplinary sources indicating a strong applied focus. Leading countries in this research field benefit from clear technology transfer policies, and the prevalent terms “production” and “biomass” underscore the industrial relevance. Key research areas include biofuels and bioremediation, with a combined emphasis that is often studied in cultivation and biomass production. Bioactive compounds derived from microalgae are a current trend for industrial, medical, and food applications. Although the potential for CO2 capture is acknowledged, direct studies are limited. This systematic review provides a comprehensive overview of current trends and identifies opportunities and challenges in microalgae research, highlighting its significance for sustainable development and industrial applications.